2015
DOI: 10.1089/cren.2015.29012.dop
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Proximal Ureteropyelostomy After Unsuccessful Endourologic Management of Complicated Proximal Ureteral Stone Disease

Abstract: We present a clinical case of a 66-year-old female with a left ureteropelvic junction impacted renal calculi associated with a tortuous ureter. After a failed combined retrograde and antegrade endoscopic procedure, a robot-assisted laparoscopic ureteropyelostomy was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Since 2005, 22 articles for RALS-UL have been published in the adult population for management of various conditions: concomitant management of UPJO and nephrolithiasis (4), concomitant management of caliceal diverticuli with stones (2), pyelolithotomy (2), pyelolithotomy with nephrolithotomy (1), extended pyelolithotomy (4), ureterolithotomy (1 proximal, 1 distal), anatrophic nephrolithotomy (3), and management of stones when ectopic and other renal anomalies are present (2 pelvic kidney, 1 horseshoe kidney, 1 cross-fused ectopic kidney). Of note, many of these studies did not include detailed information regarding the initial patient stone burden.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2005, 22 articles for RALS-UL have been published in the adult population for management of various conditions: concomitant management of UPJO and nephrolithiasis (4), concomitant management of caliceal diverticuli with stones (2), pyelolithotomy (2), pyelolithotomy with nephrolithotomy (1), extended pyelolithotomy (4), ureterolithotomy (1 proximal, 1 distal), anatrophic nephrolithotomy (3), and management of stones when ectopic and other renal anomalies are present (2 pelvic kidney, 1 horseshoe kidney, 1 cross-fused ectopic kidney). Of note, many of these studies did not include detailed information regarding the initial patient stone burden.…”
Section: Resultsmentioning
confidence: 99%
“…It's use in the upper urinary tract with good outcomes has been previously reported (41). In 2015 Olvera-Posada et al (3) reported the case of a 66-year-old female with a history of recurrent ureterolithiasis, recurrent urinary tract infections (UTIs), two large obstructing right proximal ureteral calculi, and a right split renal function of 37%. Despite a remote successful ureteroscopy in the past on that same kidney, the patient underwent failed attempts at antegrade or retrograde access to the stone in this instance; partially due to ureteral tortuosity and significant inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation